2020
DOI: 10.1177/1090198120935073
|View full text |Cite
|
Sign up to set email alerts
|

How Fear Appeal Approaches in COVID-19 Health Communication May Be Harming the Global Community

Abstract: As health professionals develop health communication for coronavirus disease 2019 (COVID-19), we implore that these communication approaches do not include fear appeals. Fear appeals, also known as scare tactics, have been widely used to promote recommended preventive behaviors. We contend that unintended negative outcomes can result from fear appeals that intensify the already complex pandemic and efforts to contain it. We encourage public health professionals to reevaluate their desire to use fear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 18 publications
2
114
1
1
Order By: Relevance
“…First, the results showed that public health education significantly reduced the fear of COVID‐19 among nurses through health education. This outcome is in line with that reported by Stolow, Moses, Lederer, and Carter (2020). The result is an extension of that depicted by Bibi (2019), whereby awareness of basic health issues, such as hypertension, cholesterol, and cardiovascular disease, can reduce the risk of one’s vulnerability towards these diseases.…”
Section: Discussionsupporting
confidence: 93%
“…First, the results showed that public health education significantly reduced the fear of COVID‐19 among nurses through health education. This outcome is in line with that reported by Stolow, Moses, Lederer, and Carter (2020). The result is an extension of that depicted by Bibi (2019), whereby awareness of basic health issues, such as hypertension, cholesterol, and cardiovascular disease, can reduce the risk of one’s vulnerability towards these diseases.…”
Section: Discussionsupporting
confidence: 93%
“…However, research on fear appeals suggests that such appeals are only effective under ideal conditions (e.g., when self‐efficacy is high among message recipients, which is rarely the case; Kok, Peters, Kessels, Ten Hoor, & Ruiter, 2018), and are very likely to cause an array of unintended consequences (e.g., rejection of the threatening health message; Ruiter, Kessels, Peters, & Kok, 2014). The evidence against fear appeals is so strong, in fact, that Stolow, Moses, Lederer, & Carter, 2020 urged health professionals to not use fear appeals in COVID‐19 health communication, noting that “The world's health depends on it” (p. 534). Unfortunately, the TMHM‐P offers no rebuttal to these critiques of fear appeals.…”
Section: Terror Management Perspectivesmentioning
confidence: 99%
“…Safety measures for COVID-19 meant shifting norms and behaviors, such as abandoning hand shaking and adopting masks, had to be incorporated quickly and tailored to the unique needs of each audience. The organizations informing these cases studies created multimedia activities adapted to local culture(s) and applied positive message framing with actionable solutions, ideas supported by research (Brusse et al, 2017;Stolow et al, 2020).…”
Section: Takeaway #2: Considering Lessons Learned From These Ee Case mentioning
confidence: 99%